Characterization of mannanase from Bacillus circulans NT 6.7 and its application in mannooligosaccharides preparation as prebiotic - Pangsri, Phanwipa; Piwpankaew, Yotthachai; Ingkakul, Arunee; Nitisinprasert, Sunee; Keawsompong, Suttipun (SpringerPlus, 2015)
This study focused on the characterization of mannanase from Bacillus circulans NT 6.7 for mannooligosaccharides (MOS) production. The enzyme from B. circulans NT 6.7 was produced using defatted copra meal as a carbon source. The mannanase was purified by ultrafiltration and column chromatography of Q-Sepharose. The purified protein (M1) was a dimeric protein with a 40 kDa subunit. The purified M1 exhibited optimum pH and temperature at pH 6.0 and 60 °C, respectively. It was activated by Mn 2+, Mg 2+, and Cu 2+ , and as inhibited by EDTA (45–65 %). The purified enzyme exhibited high specificity to beta-mannan: konjac (glucomannan), locust bean gum (galactomannan), ivory nut (mannan), guar gum (galactomannan) and defatted copra meal (galactomannan). The defatted copra meal could be hydrolyzed by purified M1 into mannooligosaccharides which promoted beneficial bacteria, especially Lactobacillus group, and inhibited pathogenic bacteria; Shigella dysenteria DMST 1511, Staphylococcus aureus TISTR 029, and Salmonella enterica serovar Enteritidis DMST 17368. Therefore, the mannanase from B. circulans NT 6.7 would be a novel source of enzymes for the mannooligosaccharides production as prebiotics.